COLLABORATIVE GOVERNANCE DALAM PENGELOLAAN SAMPAH DI WILAYAH KECAMATAN PULAU TIGA BARAT KABUPATEN NATUNA - Idris, Idris; Herdiana, Dian; Mujtahid, Iqbal Miftakhul (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
Because waste management has the potential to affect public health, the role and process of waste management need collaboration between policymakers and implementers of existing waste management efforts. The objective of this research was to evaluate and analyze collaborative governance in the district of Pulau Tiga Barat, Natuna Regency, with the goal of resolving waste management issues. This study employs a qualitative method in conjunction with a descriptive approach. Primary and secondary data sources were used in this investigation. The study's findings reveal that collaborative governance in waste management in the Pulau Tiga Barat District has been operating relatively well, as evidenced by the Starting Condition, Collaborative Process, Facilitative Leadership, and Institutional design. Additionally, the issues that impede the collaborative process are reflected in financial statistics, most notably the district of Pulau Tiga Barat's insufficient budget allocation for trash management